2017
DOI: 10.3390/microorganisms5040073
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Peculiarities of Lignin-Modifying Enzyme Production by the White-Rot Basidiomycete Coriolopsis gallica Strain BCC 142

Abstract: Sixteen white-rot Basidiomycota isolates were screened for production of lignin-modifying enzymes (LME) in glycerol- and mandarin peel-containing media. In the synthetic medium, Cerrena unicolor strains were the only high laccase (Lac) (3.2–9.4 U/mL) and manganese peroxidase (MnP) (0.56–1.64 U/mL) producers while one isolate Coriolopsis gallica was the only lignin peroxidase (LiP) (0.07 U/mL) producer. Addition of mandarin peels to the synthetic medium promoted Lac production either due to an increase in funga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
2
11
0
2
Order By: Relevance
“…A similar increase in Lac production in response to the addition of glycerol has been reported about different whiterot fungi [22,53]. Similar data have been published on LiP activity of Coriolopsis gallica cultivated in the presence of Tween 80 [55]. In agreement with these findings, both substances were described as good inducers for the production of MnP using Daedaleopsis confragosa, Fomes fomentarius, T. gibbosa, T. suaveolens and T. versicolor [52], Stereum ostrea [11], Phanerochaete chrysosporium [21].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A similar increase in Lac production in response to the addition of glycerol has been reported about different whiterot fungi [22,53]. Similar data have been published on LiP activity of Coriolopsis gallica cultivated in the presence of Tween 80 [55]. In agreement with these findings, both substances were described as good inducers for the production of MnP using Daedaleopsis confragosa, Fomes fomentarius, T. gibbosa, T. suaveolens and T. versicolor [52], Stereum ostrea [11], Phanerochaete chrysosporium [21].…”
Section: Discussionsupporting
confidence: 86%
“…Unlike most published reports [11,54], our results showed that veratryl alcohol slightly affected LiP activity of T. trogii, while glycerol and Tween 80 strongly reduced this activity. Similar data have been published on LiP activity of Coriolopsis gallica cultivated in the presence of Tween 80 [55]. Tonon and Odier [56] and Valli et al [57] suggested that veratryl alcohol does not stimulate higher enzyme activity by inducing de novo protein synthesis, but protects the enzyme from inactivation by excess H 2 O 2 produced by the fungus in the culture.…”
Section: Discussionsupporting
confidence: 74%
“…Fabrini et al (2016) relataram que Research, Society and Development, v. 9, n. 12, e12391210942, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i12.10942 a adição de melaço de soja, apesar da elevada concentração de açúcares fermentescíveis, não alterou a atividade de lacase de Pycnoporus sanguineus resultados que estão de acordo com os observados no presente estudo. Apesar de rico em açúcares, o que para algumas espécies de fungos pode favorecer a atividade de lacase, outros componentes do MS podem afetar negativamente o micélio e a atividade enzimática (Elisashvili et al, 2017).…”
Section: Resultsunclassified
“…são espécies de fungos da podridão branca e, por isso, podem crescer em substratos lignocelulósicos devido à capacidade de degradar todos os componentes da parede celular vegetal, produzindo enzimas extracelulares para a Research, Society andDevelopment, v. 10, n. 1, e6810111406, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i1.11406 degradação da lignina, celulose e hemicelulose (Knop et al, 2015;Ravindran et al, 2018). As principais enzimas desse complexo são hidrolases (celulases e hemicelulases) e ligninases (fenol oxidases e peroxidases) (Elisashvili et al, 2017). Estas classes de enzimas degradam a parede celular vegetal fornecendo ao fungo nutrientes como carbono, nitrogênio, enxofre, entre outros; fazendo com que os fungos tenham habilidade de crescer em diferentes substratos (Bellettini et al, 2019).…”
Section: Introductionunclassified